Development of Local Wisdom at Bahulak Market in Karungan Tourism Village - Kris Cahyani Ermawati (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
The development of the Pasar Bahulak local market in the Karungan Village Tourism Desa in the Sragen Regency has been hindered. One reason for this is the lack of optimal development in the Pasar Bahulak local market. Therefore, the Pasar Bahulak needs to be developed for local Wisata tourism based on its locality. This study aimed to describe the development, supporting factors, and obstacles of Pasar Bahulak based on locality. This study used a qualitative method. The data collection techniques used in this study were interviews and direct observation. Validity was conducted through triangulation of data sources. The informants in this research were the managers of three tourism villages in Desa Wisata.